TOKSISITAS AKUT EKSTRAK ETANOL DAUN KIRINYUH (CHROMOLAENA ODORATA (L) R.M. KING & H. ROB) PADA MENCIT PUTIH JANTAN - Nirwanto .; Aried Ariadi; Helmi Arifin (Jurnal Ilmu Kesehatan dan Kesehatan, 2017)
Abstract: The acute toxicity of ethanol extracts from Kirinyuh (Chromolaena odorata (L) R.M.King & H. Rob) leaves to white mice males has been done. Parameters toxicity observed were LD50and delayed toxic effects for 14 days of observation including changes in weight, volume of waterconsumption, and relative weight of the organs like heart, liver, kidneys, stomach and lungs. Theethanol extract of Chromolaena odorata (L) R.M King & H. Rob leaves orally at a dose of 4 g/kgBB,8 g/kgBB and 16 g/kgBB, showed that was categorized practically non-toxic (LD50> 15 g/kgBB).Delayed toxic effects are seen from the significant differences in body weight, the volume of water,relative organ weight of lung and stomach (P<0.05). There were no significant differences in therelative organ weight of the heart, liver and kidneys (P<0.05).